Where is the Love, y'all? Punk Pedagogy in High School Choir. Issue 1 (May 2023) - Lee, Austina Frances; Smith, Gareth Dylan
Capitalism and its offspring, neoliberalism, are omnipresent in modern and postmodern societies. Illich, Giroux, and McLaren, among others, point to the futility and inequity of current models of education that focus on standardization, vocationalism, and conformity. Running counter to these powerful hegemonic systems, critical pedagogues and educational philosophers such as hooks and Silverman follow philosophers Frankfurt and Wolf in identifying a teaching approach rooted in love. Such an ethic embodies a robust, punk confrontation to potentially damaging, dehumanizing institutional norms perpetrated by current systems of schooling (Hewitt & Smith, 2020). The authors present and discuss vignettes as a duoethnographic study of one teacher's work with a high school choir in Colorado Springs, USA, through which she works to engage young people as compassionate artistic citizens (Elliott & Silverman, 2015; Hendricks 2018). By teaching with love and by modeling love, she teaches young people to love, embracing what Noddings (2005) identifies as an ethic of care. This choral community demonstrates the messy, anarchist ideal that Wright (2019) highlights as a necessary future for music education, wherein the educator diverts from teaching solely to standardized expectations to address the affiliative needs of her students through a love that desires good for her students (Fromm, 1956; Noddings, 2005)